Empowering smokers with a web-assisted tobacco intervention to use prescription smoking cessation medications: a feasibility trial. (December 2015) - Selby, Peter; Hussain, Sarwar; Voci, Sabrina; Zawertailo, Laurie
Abstract Background Varenicline and bupropion, efficacious smoking cessation medications, have had suboptimal impact due to barriers at the patient, practitioner and system level. This study explored the feasibility of a web-assisted tobacco intervention offering free prescription smoking cessation medication by mail if the smoker visited a physician for authorization. Methods Adult Ontarians, smoking at least 10 cigarettes daily, intending to quit within 30 days, with no contraindications to bupropion or varenicline were eligible. After an online assessment, eligible participants received an electronic personalized printable prescription form for a 12-week course of varenicline or bupropion to bring to a physician within 3 weeks for authorization, if appropriate. The physician's office faxed prescriptions to an online pharmacy that couriered medication to the patient following medication counselling by telephone. Weekly motivational emails were sent during treatment. Participants were asked to complete follow-up questionnaires online at 7, 11, 15 and 41 weeks after enrollment. Results In total, 1214 individuals submitted an online assessment from April to September 2010 and 73.6 % (95 % confidence interval (CI) = 71.1–76.1 %;n  = 893) were eligible. At least 65.8 % (95 % CI = 62.7–68.9 %;n  = 588) of eligible participants subsequently visited a physician and 58.7 % (95 % CI = 55.5–61.9 %;n  = 524) received medication (50.6 % varenicline [n  = 265] and 49.4 % bupropion [n  = 259]). Reasons for not filling a prescription were failure to visit a physician (80.1 %; 95 % CI = 73.8–86.5 %;n  = 121), physician not prescribing the medication (15.9 %; 95 % CI = 10.1–21.7 %;n  = 24) or other reasons (4.0 %; 95 % CI = 0.9–7.1 %;n  = 6). Follow-up response rate was 66.7 % (95 % CI = 63.7–69.8 %;n  = 596). Minimal issues were encountered with printing the prescription or medication delivery. Conclusions This study establishes the feasibility of using the Internet and free medication to enable smokers to engage physicians to treat this addiction. Implementation of this intervention can be scaled up by leveraging existing healthcare systems to treat smokers on a population level. Further evaluation in a randomized controlled trial is necessary. Trial registration ClinicalTrials.gov IdentifierNCT01023659